THE NEW FACET LEADERSHIP STYLE AND SECONDARY SCHOOLS PERFORMANCE IN MAURITIUS - Subrun, Veerunjaysingh; Subrun, Leena (INTI International University, 2022)
In this new era, where the quest for a holistic education has been in the limelight, the utilization of the appropriate leadership styles in managing the different types of arising circumstances have turned out to be of utmost importance. The leadership styles of the school leaders determine the sustainability and future of all institutions. The Government of Mauritius is investing massively in the education sector in quest of quality education (Subrun &Subrun, 2015) in terms of performance. The aim of the study is to analyse the implication of the educational leadership styles in terms of the New Facet Leadership style in enhancing secondary school performance in the Mauritian education sector. It analyses the impact of the various socio-psychological in relation to the New Facet Leadership Style, work culture, the attitude of the members towards their job, occupational self-efficacy, self-concept, perception, quality of work-life, satisfaction and participation of the followers in the non-work-related activities on learners’ achievement and school performance, in the non-profit-making state and private secondary schools in Mauritius. The research work follows the characteristics of both descriptive and causal research designs, for the first part of the study, the researcher employed descriptive research and to test the hypothesis, the researcher employed the causal research design. Data has been gathered from 96 school leaders and 404 educators of both state and private secondary schools. The data was analyzed using SPSS and SPSS AMOS. The present study is the foremost study that uses the Structural Equation Modeling in the analysis of the New Facet Leadership Style (composed of Contingency leadership, Managerial Leadership, Participative leadership, Instructional Leadership and Moral leadership, along with the transformational leadership style). Structural Equation Modeling is used as the new confirmatory tool to confirm that the New Facet Leadership Style based on the contingency and transformational leadership theories practised by the leaders positively affects the performance of the learner’s achievements. Thus, this study acts and sets benchmarks for other scholars to further investigate the concept of leadership styles in terms of the New Facet Leadership Style, performance and learner’s performance at the National and International levels using Structural Equation Modeling as the main tool of analysis at various level of the educational system.